A new species of the armored catfish Parotocinclus (Loricariidae: Hypoptopomatinae), from the Amazon basin in Colombia - Lehmann A.,Pablo (2015)
A new species of hypoptopomatine cascudinho is described from a creek tributary to the Amazon River in Leticia, Amazonas Departament, Colombia. The new species of Parotocinclus is distinguished from congeners from northeastern to southeastern Brazilian rivers in having the cheek canal plate elongated posteriorly on the ventral surface of head and contacting the cleithrum. It is diagnosed from P. collinsae (Essequibo River basin, Guiana) and P. halbothi (rio Trombetas basin, Brazil and Marowijne River, Suriname), by having a triangular patch of dark pigmentation on the anterior portion of the dorsal-fin membrane, by the absence of unicuspid accessory teeth on both the premaxilla and dentary, and by having a Y-shaped light mark on the snout. The new species of Parotocinclus is distinguished from all remaining congeners by having a pigmentation pattern consisting of conspicuous dark dots smaller than a pupil diameter, broadly distributed dorsally and ventrally.